Leading Question as a Category of Forensic Linguistic Examination - A. Baranov (Теория и практика судебной экспертизы)
The article discusses the phenomenon of a leading question as an object of forensic linguistic examination. It shows that the leading question (i) contains semantic information in the form of a proposition (propositional criterion), (ii) brings information within the field of a respondent’s view (relevance criterion), and (iii) reflects the version of the described events that is desirable for an inquirer (engagement criterion). Linguistic examination allows to conclude on the fulfillment of the propositional criterion and the criterion of relevance. The criterion of engagement refers to extralinguistic knowledge and can rarely be proven as the result of the corresponding discourse analysis by linguistic instruments only. The paper analyses the examples of leading questions’ functioning in real discourse including their use in interrogations at the investigative stage and in court hearings. It highlights those segments of the semantics of ‘yes/no-’ and ‘wh-questions’ that are most often used by experienced communicators toconvey their ideas on the most likely answer to the interlocutor. Related phenomena of investigative and judicial discourse are also discussed: tips and “augmented reality” situations.The phenomenon of the leading question should be considered as the interdisciplinary one, having not only linguistic, but also psychological and legal aspects. From the methodological point of view, linguistic examination allows to identify only the linguistic features of leading questions proper – presence of a proposition and relevance (introduction of information into the view field of an addressee). Engagement as a feature of the leading question lies beyond the scope of linguistic knowledge.